2018
DOI: 10.25115/ejrep.v10i28.1532
|View full text |Cite
|
Sign up to set email alerts
|

The role of mathematical homework and prior knowledge on the relationship between students’ mathematical performance, cognitive style and working memory capacity

Abstract: Introduction. The main objective of this study is (a) to investigate whether cognitive styles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 69 publications
1
9
0
3
Order By: Relevance
“…FI more expert problem solver than FD [12]. Besides that, these results are consistent with the results of research [13] which showed that mathematical performances are predicted by cognitive style FI and FD.…”
Section: Discussionsupporting
confidence: 81%
“…FI more expert problem solver than FD [12]. Besides that, these results are consistent with the results of research [13] which showed that mathematical performances are predicted by cognitive style FI and FD.…”
Section: Discussionsupporting
confidence: 81%
“…The majority of students (78.6%) agreed that periodic assignment in EAP class was fun because it had a various form of assignments such as a written assignment, video assignment, and project assignment. Paulu (1998, as cited in Mousavi et al, 2012) suggested that to vary the assignment in order to make the assignment is pleasant and enjoyable to do.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a lecturer is a planner, facilitator, and evaluator. In order to optimize the assignment as the assessment tool, the lecturer must consider Paulu's (1998, as cited in Mousavi et al, 2012) suggestion about varying the assignment types to make it pleasant and enjoyable for the students. Besides, after providing the assignment, the lecturer shall not leave his/her students to accomplish the assignment given on their own without further guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Nicolaou and Xistouri (2011) stated that "In order to avoid the different criteria found in the literature for discriminating between field-dependent and field-independent participants, the Alamolhodaei's study uses a statistical technique for the discrimination"(p.5). And so, this method is often preferred because it produces more valid and reliable results in cognitive style researches (Aydin, 2015;Cataloglu & Ates, 2014;Mousavi, Radmehr & Alamolhodaei, 2012). In this method, the students who find more correct shapes than the number obtained as a result of adding one-quarter of the standard deviation of the scores obtained, are classified as fielddependent, and the students who find less correct shape than the number obtained by subtracting one-quarter of the standard deviation from the average are classified as field-dependent.…”
Section: Data Collection Toolsmentioning
confidence: 99%